IMPLEMENTASI MANAJEMEN PENDIDIKAN ISLAM BERBASIS AL-QUR'AN DAN SUNNAH - Adiyono Adiyono (CV. ADIBA AISHA AMIRA, 2025)
This research aims to investigate and analyze the implementation of Islamic education management based on the Koran and Sunnah in the context of modern education. This approach is expected to make a positive contribution to the development of student character, morality and academic achievement. The library research method is used to collect data from library sources such as books, journals and scientific articles that are relevant to the research subject. The research results show that the implementation of Islamic education management based on the Koran and Sunnah has succeeded in integrating Islamic values into all aspects of education. Students who follow education with this approach show improved character and morality, while achieving improved academic skills. The discussion involves the relevance of the concept of Islamic education management, the challenges that may be faced, as well as the implications and impact on society. These findings provide an in-depth view of the importance of combining the principles of the Qur'an and Sunnah in the management of Islamic education to achieve education that is holistic and in accordance with Islamic values. The implications of this research can be a guide for Islamic educational institutions in increasing the effectiveness of their management approaches in order to produce a generation with character, ethics and competitiveness.